Silicon nitride sintered substrate and manufacturing method thereof
Patent Information
- Application Number
- JP2023143320
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-17
AI Technical Summary
【0011】 本発明の窒化ケイ素焼結基板は、破壊靭性と曲げ強度のいずれの特性においても優れた特性を発揮することができる。
Smart Images

Figure 2025036793000002 
Figure 2025036793000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel silicon nitride sintered substrate. [Background technology]
[0002] Silicon nitride sintered substrates have been attracting attention as a ceramic material in various industrial fields due to their excellent properties such as high thermal conductivity, high insulation, and high strength. For example, they are used as heat dissipation substrates for power modules for automobiles and semiconductors.
[0003] Among these, when used as a heat dissipation substrate, high fracture toughness and bending strength are required. However, it is usually difficult to achieve both of these physical properties. For example, a silicon nitride sintered substrate that has silicon nitride sintered particles with a large equivalent circle diameter and has achieved high fracture toughness tends to have low bending strength (see Patent Document 1), while conversely, a silicon nitride sintered substrate that has silicon nitride sintered particles with a small equivalent circle diameter to achieve high bending strength tends to have low fracture toughness (see Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2023-043818 [Patent Document 2] Japanese Patent Application Publication No. 11-100276 Summary of the Invention [Problem to be solved by the invention]
[0005] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a silicon nitride sintered substrate which achieves both high fracture toughness and high bending strength. [Means for solving the problem]
[0006] In order to solve the above problems, the inventors of the present invention have conducted extensive research and have found that by forming raw material powders that exhibit different behaviors into layers and sintering them into a sintered body formed from the materials constituting a silicon nitride sintered substrate, the properties of each sintered body can be exhibited without mutual inhibition. Based on this knowledge, the inventors have conducted further research and found that a sintered body obtained by stacking a green body mainly composed of β-silicon nitride powder on a green body mainly composed of α-silicon nitride powder and firing the stack results in a sintered substrate that is excellent in both fracture toughness and bending strength, which has led to the completion of the present invention.
[0007] That is, according to the present invention, there is provided a silicon nitride sintered substrate, characterized in that the silicon nitride sintered substrate comprises a surface layer present on both surfaces and consisting of silicon nitride sintered particles having an average equivalent circular diameter of 2.0 to 10.0 μm and an average aspect ratio of 3 or more, and an inner layer present on both surfaces and consisting of silicon nitride sintered particles having an average equivalent circular diameter of 5.0 μm or less and an average aspect ratio of less than 3.
[0008] It is preferable that the thickness of each surface layer of the sintered silicon nitride substrate is 0.01 mm or more, and the total thickness of both surface layers is 35% or less of the thickness of the sintered silicon nitride substrate.
[0009] The thickness of the sintered silicon nitride substrate is preferably 0.1 to 1.0 mm.
[0010] The present invention also provides a method for producing the above-mentioned sintered silicon nitride substrate, which comprises forming layers made of silicon nitride green bodies mainly made of α-type silicon nitride powder on both surfaces of a layer made of silicon nitride green bodies mainly made of β-type silicon nitride powder, and then firing the layers. Effect of the Invention
[0011] The silicon nitride sintered substrate of the present invention can exhibit excellent properties in both fracture toughness and bending strength. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic diagram showing an example of an apparatus used in the production method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The silicon nitride sintered substrate of the present invention is a silicon nitride sintered substrate characterized in that it comprises a surface layer on both surfaces, which is made of silicon nitride sintered particles having an average equivalent circular diameter of 2.0 to 10.0 μm and an average aspect ratio of 3 or more, and an inner layer, which is made of silicon nitride sintered particles having an average equivalent circular diameter of 5.0 μm or less and an average aspect ratio of less than 3.
[0014] In the present invention, the average equivalent circular diameter is the average value of the equivalent circular diameters based on the area, and the average aspect ratio is the average value of the aspect ratios based on the area.
[0015] The mechanism by which the sintered substrate of the present invention exerts the above-mentioned effects is not clear, but the inventors presume that the high aspect ratio sintered silicon nitride particles produced by sintering α-type silicon nitride powder are present in the surface layer of the sintered silicon nitride substrate, thereby exhibiting high fracture toughness, and the low aspect ratio sintered silicon nitride particles produced by sintering β-type silicon nitride powder are present in the internal layer, thereby exhibiting high bending strength, and that these layers are integrated without interfering with each other and act as a characteristic of the entire substrate.
[0016] The surface layers formed on both surfaces of the silicon nitride sintered substrate have an average equivalent circular diameter of 2.0 to 10.0 μm, preferably 3.0 to 8.0 μm, and more preferably more than 5.0 μm and 8.0 μm or less. If the average equivalent circular diameter is smaller than the above range, the improvement in fracture toughness of the silicon nitride sintered substrate becomes insufficient, and if it exceeds the above range, the surface roughness becomes large, and there is a risk of problems such as poor bonding occurring when forming a metallized layer on the silicon nitride sintered substrate.
[0017] The surface layers formed on both surfaces of the silicon nitride sintered substrate have an average aspect ratio of 3 or more, preferably 4 or more. If the average aspect ratio of the surface layers is smaller than the above range, sufficient fracture toughness cannot be achieved. The average aspect ratio of the surface layers may be within the above range, but from the viewpoint of manufacturing, it is preferable that the average aspect ratio is 20 or less, particularly 10 or less.
[0018] The thickness of each layer of the surface layer is 0.01 mm or more, preferably 0.02 mm or more, and the total thickness of both surface layers is 35% or less, preferably 25% or less, more preferably 20% or less, particularly preferably 15% or less of the thickness of the silicon nitride sintered substrate. If the thickness of the surface layer is less than 0.01 mm, it is difficult to obtain a sufficient effect in terms of fracture toughness, and if the thickness of the surface layer exceeds the range of the silicon nitride sintered substrate, the thickness of the inner layer becomes relatively thin, and as a result, the bending strength tends to decrease.
[0019] In the present invention, the average equivalent circle diameter of the silicon nitride sintered grains constituting the inner layer of the silicon nitride sintered substrate is 5.0 μm or less, preferably 4.0 μm or less. That is, if the average equivalent circle diameter is larger than the above range, the improvement in bending strength becomes insufficient, and the object of the present invention cannot be achieved. In addition, the lower limit of the average equivalent circle diameter is not particularly limited, but in industrial implementation, about 0.5 μm is suitable. In addition, the aspect ratio of the silicon nitride sintered grains constituting the inside of the silicon nitride sintered substrate is less than 3, preferably less than 2. If the average aspect ratio of the silicon nitride sintered grains in the inside is 3 or more, sufficient bending strength cannot be exhibited.
[0020] In the silicon nitride sintered substrate of the present invention, depending on the conditions of the manufacturing method described later, an intermediate layer having an intermediate value between the circle equivalent diameter and aspect ratio of the surface layer and the inner layer may be present at the interface between the surface layer and the inner layer, and the present invention also includes an embodiment in which such an intermediate layer is present. The thickness of the intermediate layer may vary slightly depending on the manufacturing method described later, but may be 5% or less, particularly 2% or less, of the silicon nitride sintered substrate.
[0021] The silicon nitride sintered substrate of the present invention may have a thickness of 0.1 to 1.0 mm, and preferably 0.2 to 0.5 mm. The area of the substrate is 1 to 500 cm. 2 , especially 5~300cm 2 It may be.
[0022] The method for producing the silicon nitride sintered substrate of the present invention is not particularly limited, but a typical method is to form surface layers made of silicon nitride green bodies (hereinafter also referred to as α-type green bodies) mainly made of α-type silicon nitride powder on both surfaces of a layer made of silicon nitride green bodies (hereinafter also referred to as β-type green bodies) mainly made of β-type silicon nitride powder, and then sinter the layers. In the above method, the thickness of each layer of the green bodies may be determined taking into consideration the thickness of the surface layer and the inner layer after sintering.
[0023] In the above-mentioned manufacturing method, the silicon nitride powder constituting the β-type green body may be 80% by mass or more, preferably 90% by mass or more, of β-type silicon nitride powder, with the remainder being α-type silicon nitride powder. Also, the silicon nitride powder constituting the α-type green body may be 80% by mass or more, preferably 90% by mass or more, of α-type silicon nitride powder, with the remainder being β-type silicon nitride powder.
[0024] In the present invention, the green body may have any known composition without any particular limitation. Specifically, each silicon nitride powder may contain an organic binder for molding, a sintering aid, and, if necessary, an antifoaming agent, a plasticizer, a dispersing agent, etc.
[0025] The binder is not particularly limited, but examples thereof include polyvinyl alcohol, polyvinyl butyral, methyl cellulose, alginic acid, polyethylene glycol, carboxymethyl cellulose, ethyl cellulose, and acrylic resins.
[0026] The content of the binder used in producing the green body is preferably 1 to 30 parts by mass with respect to 100 parts by mass of the silicon nitride powder, and the ratio may be appropriately determined depending on the molding method.
[0027] In addition, the sintering aid can be any known sintering aid without any particular limitations. For example, yttria (Y2O3), magnesia (MgO), ceria (CeO), etc. are common. In addition, sintering aids without oxygen bonds can also be used, and the use of such sintering aids is preferable because it can suppress the decrease in thermal conductivity of the resulting silicon nitride sintered substrate due to oxygen. As the sintering aid without oxygen bonds, a carbonitride-based compound containing a rare earth element or a magnesium element (hereinafter referred to as a carbonitride-based sintering aid) is preferable. In the carbonitride-based compound containing a rare earth element, the rare earth element is preferably Y (yttrium), La (lanthanum), Sm (samarium), Ce (cerium), Yb (ytterbium), etc. Examples of carbonitride-based sintering aids include Y2Si4N6C, Ce2Si4N6C, MgSi4N6C, etc.
[0028] The sintering aid may be used alone or in combination of two or more kinds. The sintering aid is preferably used in an amount of 1 to 20 mass %, particularly preferably 3 to 10 mass %, based on 100 parts by mass of the silicon nitride powder.
[0029] In the present invention, the manner in which the α-type green body layers are formed on both surfaces of the β-type green body layer is not particularly limited. Representative manners include a method (Method A) in which a slurry having the composition of an α-type silicon nitride green body is applied to both surfaces of the β-type green body layer (inner layer) and dried to form a layer (surface layer) made of the α-type green body, and a method (Method B) in which a layer (surface layer) made of the α-type green body is laminated on both surfaces of the β-type green body layer (inner layer).
[0030] To explain the above-mentioned method A in more detail, the layer of the β-type green body may be obtained, for example, by forming a molding composition having the composition of the above-mentioned green body into a sheet by a known molding means. Hereinafter, the above-mentioned green body formed into a sheet shape may be referred to as a "green sheet".
[0031] Examples of the molding method include press molding, extrusion molding, injection molding, doctor blade, etc., and the doctor blade method is particularly preferred. In this case, the molding composition may contain a solvent from the viewpoint of ease of handling and molding. The solvent is not particularly limited, and examples thereof include organic solvents such as alcohols and hydrocarbons, and water. Such a solvent is removed by drying after molding.
[0032] The slurry to be applied to both surfaces of the layer of the β-type green body can be prepared from a molding composition having the composition of the α-type green body and the solvent. The slurry can be applied by brush coating, spray coating, or by using a coating device such as a roll coater. Alternatively, a method can be used in which the layer made of the β-type green body is used as a base and the slurry is applied to the surface of the layer by a doctor blade method.
[0033] To explain the above-mentioned method B in more detail, a molding composition having the composition of the green bodies for constituting the surface layer and the inner layer is molded into a sheet by a known molding means to obtain green sheets of each silicon nitride powder, and then a green sheet made of an α-type green body is laminated on both surfaces of the green sheet made of a β-type green body via an adhesive liquid. As the adhesive liquid, a solvent alone can be used, but a slurry prepared by adding silicon nitride powder and, if necessary, a binder, a sintering aid, etc. to a solvent is preferably used. In the above slurry, the silicon nitride powder may be an α-type or a β-type, or may contain both. Furthermore, since there is a risk of reducing the strength, insulation resistance, etc. of the silicon nitride sintered substrate obtained during the lamination, if air bubbles are trapped between the laminated layers, a lamination method for preventing the trapping of air bubbles between the layers is preferably a method in which, as shown in FIG. 1, a green sheet 1-a made of an α-type green body and a green sheet 1-b made of a β-type green body are fed from above between two rubber rollers that face each other horizontally and rotate downwards, and the laminated green sheets are taken out from below, and a dam 4 is provided in the valley formed by the green sheets fed between the rollers to form a reservoir 3 for the adhesive liquid. According to the above method, by forming the reservoir 3, the joint between the green sheets 1-a and 1-b is filled with the adhesive liquid, so that air bubbles are not trapped when the green sheets are wound around the rollers, and a green sheet laminate with substantially no air bubbles in the adhesive part is obtained. Here, the dam 4 is shaped to conform to the shape of the valley of the green sheets 1-a and 1-b fed between the rollers, and is provided inside both ends of the green sheets. The dam may be fixed so as to contact the green sheet, but may also be fixed with a gap therebetween to prevent leakage of the adhesive, taking into account the surface tension of the adhesive.
[0034] In addition, the lamination method described above shows a method of laminating two green sheets, but after laminating a green sheet made of an α-type green body and a green sheet made of a β-type green body, the desired lamination can be performed with the obtained laminated green sheet as 1-a and the green sheet made of the α-type green body as 1-b.
[0035] According to the above-mentioned methods A and B, it is possible to effectively prevent air bubbles from being trapped between the surface layer and the inner layer, and this is advantageous for obtaining a silicon nitride sintered substrate that does not have voids at the bonding interface.
[0036] In the method for producing a silicon nitride sintered substrate of the present invention, a laminate of green bodies obtained by forming a layer made of an α-type green body on both surfaces of a layer made of a β-type green body can be subjected to a known degreasing treatment as necessary and then fired by a known method to obtain a silicon nitride sintered substrate.
[0037] The degreasing treatment is not particularly limited, but may be performed, for example, by heating the green sheet in air or in an inert atmosphere such as nitrogen or argon to 450 to 650° C. Furthermore, firing in a firing furnace is generally used as a firing condition.
[0038] The firing temperature can be, for example, 1500 to 1900°C. The maximum firing temperature is preferably 1700 to 1800°C, and more preferably 1750 to 1800°C. By setting the firing temperature at such a high level, grain growth is promoted, making it easier to obtain a silicon nitride sintered substrate with high toughness. The holding time at the maximum temperature should be, for example, about 6 to 9 hours.
[0039] Then, as described above, the maximum temperature is maintained for a certain period of time, and then cooled.
[0040] The firing is preferably carried out under an inert gas atmosphere. Examples of the inert gas atmosphere include a nitrogen atmosphere and an argon atmosphere, and the nitrogen atmosphere is preferred. The firing may be carried out at normal pressure or under pressure. EXAMPLES
[0041] EXAMPLES In order to explain the present invention more specifically, examples are shown below, but the present invention is not limited to these examples.
[0042] In the examples, various measurements were carried out by the following methods.
[0043] (1) Average equivalent circle diameter, average aspect ratio, and thickness of each layer of silicon nitride sintered substrate Samples A and B were cut out from the silicon nitride sintered substrate, and A was polished from one surface to the center, and B was polished from the other surface to the center by 10 μm each. The surfaces after each polishing were randomly captured with a scanning electron microscope (SEM, JCM-7000, manufactured by JEOL Ltd.) under conditions of an acceleration voltage of 15 kV and an observation magnification of 5000 times, with a field area of 20 μm × 25 μm. The area circle equivalent diameter, major axis (L), and minor axis (S) of each silicon nitride sintered particle were obtained by an image analyzer attached to the SEM device, and the aspect ratio (L / S) was obtained from the above (L) and (S). The above image capture operation was repeated so that there were 200 or more silicon nitride sintered particles, and the area circle equivalent diameter and the aspect ratio were calculated as the area-based average values, respectively, which were taken as the average circle equivalent diameter and the average aspect ratio.
[0044] In addition, in the SEM images after each of the above polishing processes, the thickness at the point where the structure changed (the area circle equivalent diameter, major axis (L), minor axis (S), and aspect ratio (L / S) of the silicon nitride sintered particles changed) was confirmed and was determined as the thickness of the surface layer, intermediate layer, and inner layer, respectively.
[0045] (2) Fracture toughness The fracture toughness (MPa·m1 / 2) was calculated by the indentation fracture (IF) method from the Vickers hardness measured using an AVK-CO Vickers hardness tester manufactured by Akashi Corporation in accordance with JIS R1607:2015.
[0046] (3) Bending strength The three-point bending strength was measured using a Tensilon universal material testing machine RTI-1310 manufactured by A&D Co., Ltd. in accordance with the method of JIS R 1601. The bending strength test piece used was a plate-shaped sintered silicon nitride substrate measuring 12 mm wide x 24 mm long.
[0047] (4) Check for voids at the bonding interface A sample of C was cut out from the silicon nitride sintered substrate. The cross section of C was polished, and the surface after each polishing was observed using a SEM with an accelerating voltage of 15 kV and an observation magnification of 5000 times, taking an image of a field of view of 20 μm × 25 μm. The above field of view was observed at the bonding interface between the surface layer and the inner layer determined by method (1). The presence or absence of voids with a major axis of 10 μm or more in the above field of view was confirmed.
[0048] Example 1 Preparation of β-type green bodies β-type silicon nitride powder (average particle size (D50): 1.0 μm, specific surface area: 12 m 2 To 100 parts by mass of β-type silicon nitride powder (100 parts by mass of β-type silicon nitride powder), 3 parts by mass of Y2O3, 2 parts by mass of Y2Si4N6C, and 3 parts by mass of MgSi4N6C were added as sintering aids and mixed in a planetary ball mill to obtain a mixed raw material of β-type silicon nitride powder. Next, the mixed raw material was formed into a sheet by the doctor blade method and dried to obtain a β-type green body with a thickness of 0.37 mm.
[0049] Fabrication of laminates (Method A) α-type silicon nitride powder (average particle size (D50): 1.0 μm, specific surface area: 8 m 2 To 100 parts by mass of β-type silicon nitride powder, 3 parts by mass of Y2O3, 2 parts by mass of Y2Si4N6C, and 3 parts by mass of MgSi4N6C were added as sintering aids, and mixed in a planetary ball mill to obtain a mixed raw material of α-type silicon nitride powder. 2 A slurry of the mixed raw material of α-type silicon nitride was applied so that the amount of silicon nitride applied per unit area was 0.0026 g, and then dried to obtain a laminate.
[0050] The laminate produced by the above method was introduced into a sintering furnace and sintered under a nitrogen atmosphere at atmospheric pressure. The sintering was performed under the conditions of a maximum temperature of 1760°C and a holding time at the maximum temperature of 9 hours. The thickness was 0.3 mm and the area was 2600 cm. 2 The silicon nitride sintered substrate was obtained. The results of various evaluations of the obtained silicon nitride sintered substrate are shown in Table 1. Note that no intermediate layer was observed in the silicon nitride sintered substrate. Also, no voids with a major axis of 10 μm or more were observed at the bonding interface.
[0051] Examples 2 to 4 The thickness of the β-type green body was set to 0.34 mm (Example 2), 0.32 mm (Example 3), and 0.58 mm (Example 4). The area of the mixed raw material slurry of α-type silicon nitride was set to 1 cm. 2 A silicon nitride sintered substrate was produced in the same manner as in Example 1, except that the amount of silicon nitride applied per unit area was changed to 0.0051 g (Example 2), 0.0077 g (Example 3), and 0.0077 g (Example 4). Various evaluation results for the produced silicon nitride sintered substrates are shown in Table 1. No intermediate layer was observed in the silicon nitride sintered substrate. Also, no voids with a major axis of 10 μm or more were observed at the bonding interface.
[0052] Example 5 α-type silicon nitride powder (average particle size (D50): 0.7 μm, specific surface area: 10 m 2 / g) and β-type silicon nitride powder (average particle size (D50): 1.2 μm, specific surface area: 10 m 2 A silicon nitride sintered substrate was produced in the same manner as in Example 1, except that a 100% Cr-Al-N-O-Pt / g) was used and the thickness was changed.
[0053] The results of various evaluations of the prepared silicon nitride sintered substrates are shown in Table 1. No intermediate layer was observed in the silicon nitride sintered substrates. Also, no voids with a major axis of 10 μm or more were observed at the bonding interface.
[0054] Example 6 α-type silicon nitride powder (average particle size (D50): 0.8 μm, specific surface area: 9 m 2 / g) and β-type silicon nitride powder (average particle size (D50): 1.5 μm, specific surface area: 7 m 2 A silicon nitride sintered substrate was produced in the same manner as in Example 1, except that a 100% Cr-Al-N-O-Pt / g) was used and the thickness was changed.
[0055] The results of various evaluations of the prepared silicon nitride sintered substrates are shown in Table 1. No intermediate layer was observed in the silicon nitride sintered substrates. Also, no voids with a circle equivalent diameter of 10 μm or more were observed at the bonding interface.
[0056] Example 7 Preparation of β-type green bodies β-type silicon nitride powder (average particle size (D50): 1.0 μm, specific surface area: 12 m 2 To 100 parts by mass of β-type silicon nitride powder, 3 parts by mass of Y2O3, 2 parts by mass of Y2Si4N6C, and 3 parts by mass of MgSi4N6C were added as sintering aids and mixed in a planetary ball mill to obtain a mixed raw material of β-type silicon nitride powder. Next, the mixed raw material was formed into a sheet with a thickness of 0.40 mm by a doctor blade method and dried to obtain a β-type green body.
[0057] Fabrication of laminates (Method B) α-type silicon nitride powder (average particle size (D50): 1.0 μm, specific surface area: 8 m 2 To 100 parts by mass of β-type silicon nitride powder (100 parts by mass / g), 3 parts by mass of Y2O3, 2 parts by mass of Y2Si4N6C, and 3 parts by mass of MgSi4N6C were added as sintering aids, and mixed in a planetary ball mill to obtain a mixed raw material of α-type silicon nitride powder. Next, the mixed raw material was formed into a sheet shape of 0.20 mm in thickness by a doctor blade method, and dried to obtain an α-type green body. By the method shown in FIG. 1, a lamination operation was performed on each side of a green sheet of the β-type green body having a thickness of 0.8 mm, and a green sheet of the α-type green body was laminated on each of the two surfaces via an adhesive liquid. A slurry of the mixed raw material of α-type silicon nitride was used as the adhesive liquid.
[0058] Thereafter, a silicon nitride sintered substrate was produced in the same manner as in Example 1. The results of various evaluations of the produced silicon nitride sintered substrate are shown in Table 1. Note that no intermediate layer was observed in the silicon nitride sintered substrate. Also, no voids with a major axis of 10 μm or more were observed at the bonding interface.
[0059] Comparative Examples 1 and 2 Silicon nitride sintered substrates were produced in the same manner as in Example 1, except that the surface layer made of the α-type green body was not formed, and only the layer made of the β-type green body was used, and its thickness was adjusted to 0.40 mm (Comparative Example 1) and 0.66 mm (Comparative Example 2). Various evaluation results for the produced silicon nitride sintered substrates are shown in Table 1.
[0060] [Table 1]
[0061] The silicon nitride sintered substrates of each embodiment, which had a surface layer on both surfaces consisting of silicon nitride sintered particles with an average equivalent circular diameter of 2.0 to 10.0 μm and an average aspect ratio of 3 or more, and an inner layer consisting of silicon nitride sintered particles with an average equivalent circular diameter of 5.0 μm or less and an average aspect ratio of less than 3, had excellent properties in both fracture toughness and bending strength.
[0062] On the other hand, the silicon nitride sintered substrate of the comparative example, which did not include the surface layer, was inferior in fracture toughness. [Explanation of symbols]
[0063] 1-a, 1-b Green sheets 2-a, 2-b rollers 3. Adhesive reservoir 4 Weir
Claims
1. A silicon nitride sintered substrate, comprising: a surface layer on both surfaces of the substrate, the surface layer being made of silicon nitride sintered particles having an average equivalent circular diameter of 2.0 to 10.0 μm and an average aspect ratio of 3 or more; and an inner layer being made of silicon nitride sintered particles having an average equivalent circular diameter of 5.0 μm or less and an average aspect ratio of less than 3.
2. 2. The silicon nitride sintered substrate according to claim 1, wherein the thickness of each of the surface layers of said silicon nitride sintered substrate is 0.01 mm or more, and the total thickness of both surface layers is 35% or less of the thickness of said silicon nitride sintered substrate.
3. 2. The silicon nitride sintered substrate according to claim 1, wherein the thickness of the silicon nitride sintered substrate is 0.1 to 1.0 mm.
4. A method for producing a silicon nitride sintered substrate, comprising forming a layer of a silicon nitride green body mainly composed of α-type silicon nitride powder on both surfaces of a layer of a silicon nitride green body mainly composed of β-type silicon nitride powder, and then sintering the layer.
Citation Information
Patent Citations
Silicon nitride substrate for mounting electronic parts and its manufacture
JP1999100276A
Composite ceramic material and conjugate
JP2023043818A
Cited By
Door lock device
DE102026104450A1